Corporate social responsibility and employee outcomes: The role of country context. (4th September 2017) - McNamara, Tay K.; Carapinha, Rene; Pitt‐Catsouphes, Marcie; Valcour, Monique; Lobel, Sharon
Abstract : This study examined the association between employee perceptions of two foci of corporate social responsibility (CSR) and work attitudes in different countries. Using data collected as part of a multinational research project with a core team in the United States, we found that perceptions of externally focused CSR enactment were positively associated with employee engagement and affective commitment. Perceptions of internally focused CSR enactment were positively associated with affective commitment but not with employee engagement. Analyses across countries revealed more cultural than economic differences. For example, perceptions of internally focused CSR enactment were consistently associated with affective commitment across cultural contexts, indicating that they might serve as a general foundation for building commitment. Perceptions of externally focused CSR were more strongly associated with affective commitment in Anglo than in Confucian and Latin American countries, suggesting a need for country‐specific tailoring. Based on these results, we provided recommendations for planning and implementation of CSR.